A Documentation of Environmentally Sustainable Mosque in Malaysia - M Mohd Siraj, Suhailah; Mohd Rodzi, Khairul Asyraf; Adnan, Nor Azizah; Ismail, Alice Sabrina (International Journal of Integrated Engineering, 2023)
Numerous mosques design in Malaysia disregards the environment which makes the mosque less comfort. For the past 30 years, mosque designs in Malaysia have evolved and are primarily based on the expectations of decision makers and the public (Post Modernism period). However, there are several mosques in the twenty-first century incorporate sustainability into their design that need to be documented for future research. According to the findings, instead of Masjid Raja Haji Fisabilillah, Cyberjaya, there are 4 more mosques practise sustainable design in Malaysia. These mosques have a good sense of environmental design which gives comfort to the occupants. The study conducted qualitatively from the secondary data source and on field observation. The data is compiled through descriptive analysis of sustainable characteristic implemented in the selected mosques. The propose of this paper is to document sustainable mosques in Malaysia and contribute ideas for future mosque design. This paper will be the reference for the authors to continue detail study of the sustainable mosque in the future.